A New Natural Distribution Area of the Kasnak Oak (Quercus vulcanica [Boiss. and Heldr. ex] Kotschy): Budağan Mountain (Tavşanlı and Emet Districts, Kütahya Province) - Selahattin Polat; İsmail Ege; Erhan Aslaner (Coğrafya Dergisi)
The kasnak oak (Quercus vulcanica [Boiss. and Heldr. ex] Kotschy) is an endemic oak species in Türkiye whose largest distribution area is in the western part of the Turkish Lake District. The literature on current plant studies has emphasized some of the natural distribution areas of the kasnak oak in Türkiye to be found in the Murat, Türkmen, and Şaphane mountains in Kütahya province. The kasnak oak’s distribution is unknown regarding Budağan Mountain (İnyanı Peak 1612 m) which lies between Tavşanlı and Emet districts in western Kütahya. The field studies carried out in July 2022 on Budağan Mountain were the first to identify the presence of the kasnak oak there. Kasnak oaks are located in the dry forest area formed of junipers on land made of limestone at an altitude range of 1430-1600 m on Budağan Mountain, with dolines offering a more favorable environment in terms of humidity, especially on the northern side of the mountain. Young kasnak oak groups develop at the base of the dolines and have a height of 3-4 m Individual oaks can reach 80 cm in diameter and 12 m in length.This study involves the natural distribution of the kasnak oak, an endangered (NT) group according to the risk categories of the International Union for Conservation of Nature (IUCN), on Budağan Mountain, an area that has not been previously studied in detail. In addition, the study aims to contribute to the information about the natural distribution of this endemic species and to reveal the area’s ecological characteristics.